On the Statistical Identification of Technology Disruption - Madden, Gary; Morey, Aaron; Theoharakis, B. (Pergamon, 2012)
This study suggests a statistical procedure to identify technology disruption. Inparticular, a threshold autoregressive model enables the identification of thresholdpenetration for disruptive technology that affects the dynamic adjustment of anestablished technology. Both the magnitude and direction of the impact is identifiedby country World Bank income category in the context of the impact of (disruptive)mobile telephone diffusion on (primary) fixed-line markets. Importantly, as theprocedure only requires a short time-series for the introduced technology and canreadily be conducted on an ongoing basis.